2021
DOI: 10.1590/0103-8478cr20200545
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, genotoxic, antigenotoxic, and antineoplastic activities of apitoxin produced by Apis mellifera in Northeast, Brazil

Abstract: The objective was to evaluate the in vitro antioxidant, genotoxic, antigenotoxic, and antineoplastic activities of apitoxin produced by the bee Apis mellifera. The antioxidant activity of the apitoxin solution was evaluated using the DPPH (2,2-diphenyl-1-picrilhydrazyl) method. Genotoxic potential of apitoxin was analyzed by comparing the mean DNA damage indices (idDNA) of L929 strain fibroblasts exposed to hydrogen peroxide (H2O2 - genotoxic substance), distilled water, or apitoxin. The antigenotoxic effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The PF of the venom of A. mellifera has not shown antioxidant capacity, but in other studies, they demonstrated antioxidant capacity. Curiously, they worked with the total venom or apitoxin, having the capacity to inhibit the free radical DPPH (2,2-diphenyl-1-picrylhydrazine) between 60% and 75% of antioxidant activity [ 64 ]. In the same sense, demonstrated with the venom of A. mellifera syriaca eliminating DPPH radicals between 50 to 65% [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…The PF of the venom of A. mellifera has not shown antioxidant capacity, but in other studies, they demonstrated antioxidant capacity. Curiously, they worked with the total venom or apitoxin, having the capacity to inhibit the free radical DPPH (2,2-diphenyl-1-picrylhydrazine) between 60% and 75% of antioxidant activity [ 64 ]. In the same sense, demonstrated with the venom of A. mellifera syriaca eliminating DPPH radicals between 50 to 65% [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…BV and MEL have certain effects on a variety of prostate cancer and xenotransplantation ( Badawi, 2021 ). For example, BV produced selective antitumor effects on PC3 cells, reducing their cell viability ( Viana et al, 2021 ).…”
Section: Anticancer Effectsmentioning
confidence: 99%